1992
DOI: 10.1104/pp.99.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Activation of Membrane-Bound and Soluble CF1 by Thioredoxin

Abstract: The activation of spinach (Spinacia oleracea) chloroplast coupling factor 1 (CF(1)) by thioredoxin (ThR) was characterized using membrane-bound and soluble CF(1). Light generates an electrochemical proton gradient across the thylakoid membrane, which increases the accessibility of the disulfide bond on the gamma-subunit of CF(1) to reduced ThR. The proton gradient substantially accelerates the activation of CF(1) compared with thylakoids incubated in the dark with similar concentrations of dithiothreitol and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 0 publications
1
19
1
Order By: Relevance
“…The changes observed with the y subunit include heightened sensitivity of y to trypsinization (Moroney and McCarty, 1982;Schumann et al, 1985) and greater accessibility of Cys8' to chemical modification (McCarty and Fagan, 1973). In addition, the accessibility of the y disulfide to reducing agents, such as DTT and thioredoxin, increases (Dann and McCarty, 1992). A similar increase is also observed when E is extracted from CF,CFo.…”
mentioning
confidence: 51%
“…The changes observed with the y subunit include heightened sensitivity of y to trypsinization (Moroney and McCarty, 1982;Schumann et al, 1985) and greater accessibility of Cys8' to chemical modification (McCarty and Fagan, 1973). In addition, the accessibility of the y disulfide to reducing agents, such as DTT and thioredoxin, increases (Dann and McCarty, 1992). A similar increase is also observed when E is extracted from CF,CFo.…”
mentioning
confidence: 51%
“…It was also reported that the presence of the ⑀ subunit increases the distance between ␥-Cys 322 and Trx in the ATPase⅐Trx supercomplex without changing its dissociation constant (23). In the present work, the kinetic study of the reduction of intact CF 1 by Trx was complicated by the release of the ⑀ subunit.…”
mentioning
confidence: 61%
“…Surprisingly, it reports for the first time kinetic data about the interaction between Trx and the isolated CF 1 (with or without its ⑀ subunit). Previous data included qualitative studies of the interaction between CF 1 and different Trxs (22,23), quantitative studies of this interaction at equilibrium using fluorescent probes (23), and kinetic studies of this interaction in thylakoids (21). These different approaches are complementary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations